REPRESENTASI PEREMPUAN DAN RELASI KEKUASAAN PADA CERPEN RUMAH-RUMAH NAYLA KARYA DJENAR MAESA AYU - Lia Metha Sevita Ika Sulistiyarini; Asropah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This article aims to analyze the short story Rumah-Rumah Nayla by Djenar Maesa Ayu, featured in the collection Kasur Tanah Cerpen Pilihan Kompas 2017, using Sara Mills' critical discourse analysis approach. The story presents a complex representation of women through the main character, Nayla, who undergoes an identity shift from being a wife in an "ideal" life to an independent woman who is alienated due to past trauma. This research employs a descriptive qualitative approach with a case study method focused on Rumah-Rumah Nayla by Djenar Maesa Ayu. This approach was chosen as the study focuses on analyzing the meanings and discourse formed within the text, through a gender perspective and how the discourse constructs the position of women in a patriarchal society. By applying positionality analysis of the subject and object within Rumah-Rumah Nayla, this article explores how women are positioned as speaking subjects and as objects within the view of a patriarchal society. The results show that the story critiques traditional gender roles and illustrates the challenges women face in reclaiming agency under social dominance and personal trauma.